Mapping National Innovation Systems in the OECD Area - Markus Balzat; Andreas Pyka (Universität Augsburg, Institut für Volkswirtschaftslehre, 2005)
The purpose of this paper is to present new findings about the structure and the organization of innovative activities in selected OECD countries. By using the approach of national systems of innovation as a conceptual framework and by applying multivariate data analysis techniques, this paper aims to add new insights into the specific structures of the eighteen national systems of innovation under study. A central result from this comparative study is a categorisation of national systems of innovation into different clusters, with each cluster representing distinctive cross-national structural similarities. By accounting for sectoral specifics, the commonly taken perspective on national innovation systems is extended. Thereby, a more precise picture of the structural composition of the analyzed national innovation systems accrues. Also, a new linkage between the two approaches of national and sectoral innovation systems is created.
urn:nbn:de:bvb:384-opus4-711620
Keywords: P51; O11; C33; O31; 330; national innovation systems; comparative study; classification